RESPONSE OF SIX CHILI VARIETIES TO ANTHRACNOSE DISEASE CAUSED BY Colletotrichum acutatum AND C. gloeosporioides - Perdani, Ambar Yuswi; Paradisa, Yashanti Berlinda; Wahyuni, Wahyuni; Indrayani, Sri; Sulistyowati, Yuli; Cahyani, Yani (Universitas Lampung, 2021)
Response of six chili varieties to anthracnose disease caused by Colletotrichum acutatum and C. gloeosporioides. Chili is one of the horticultural commodities with high economic value. Chili production is constrained by anthracnose diseases. Losses due to anthracnose can reduce the fruits quality and yields lose. This study aims to determine the resistance of several chili varieties to anthracnose. Genetic material was used six varieties of chili. Ripe chilies were inoculated with two types of Colletotrichum isolates, i.e. C. acutatum and C. gleosporides. The experiment was arranged in a factorial randomized block design with three replications. The first factor were chili varieties: Laris, SSP, Habanero, Cibinong, Ekasari, and Kopay. The second factor was two types of fungal isolates. Observations were made on the incidence and severity of disease due to anthracnose. The results showed that both fungal isolates were effective in causing anthracnose disease in chilies. Habanero was very susceptible to anthracnose. Laris and Ekasari were moderately resistant to anthracnose diseases. These findings are important to develop new Capsicum cultivars that are more adaptive to anthracnose disease.